In Vitro and In Vivo Studies of the Antiparasitic Activity of Sterol 14α-Demethylase (CYP51) Inhibitor VNI against Drug-Resistant Strains of Trypanosoma cruzi - Soeiro, Maria de Nazaré Correia (American Society for Microbiology, 2013)
Chagas disease affects more than 10 million people worldwide, and yet, as it has historically been known as a disease of the poor, it remains highly neglected. Two currently available drugs exhibit severe toxicity and low effectiveness, especially in the chronic phase, while new drug discovery has been halted for years as a result of a lack of interest from pharmaceutical companies. Although attempts to repurpose the antifungal drugs posaconazole and ravuconazole (inhibitors of fungal sterol 14α-demethylase [CYP51]) are finally in progress, development of cheaper and more efficient, preferably Trypanosoma cruzi-specific, chemotherapies would be highly advantageous. We have recently reported that the experimental T. cruzi CYP51 inhibitor VNI cures with 100% survival and 100% parasitological clearance both acute and chronic murine infections with the Tulahuen strain of T. cruzi. In this work, we further explored the potential of VNI by assaying nitro-derivative-resistant T. cruzi strains, Y and Colombiana, in highly stringent protocols of acute infection. The data show high antiparasitic efficacy of VNI and its derivative (VNI/VNF) against both forms of T. cruzi that are relevant for mammalian host infection (bloodstream and amastigotes), with the in vivo potency, at 25 mg/kg twice a day (b.i.d.), similar to that of benznidazole (100 mg/kg/day). Transmission electron microscopy and reverse mutation tests were performed to explore cellular ultrastructural and mutagenic aspects of VNI, respectively. No mutagenic potential could be seen by the Ames test at up to 3.5 μM, and the main ultrastructural damage induced by VNI in T. cruzi was related to Golgi apparatus and endoplasmic reticulum organization, with membrane blebs presenting an autophagic phenotype. Thus, these preliminary studies confirm VNI as a very promising trypanocidal drug candidate for Chagas disease therapy.